Global trends and emerging insights in ocular tumor-associated metabolites: a bibliometric and visualization analysis - Cai, Subo; Xu, Wuping; Yu, Dongyi; Xia, Yimin (Frontiers in Molecular Biosciences, 2025)
ObjectiveThis study aims to perform a comprehensive bibliometric analysis of global research on ocular tumor metabolomics, identifying key research trends, influential contributors, and emerging themes from 1995 to 2024.MethodsA systematic search was conducted in the Web of Science Core Collection (WoSCC) database to retrieve publications related to ocular tumor metabolomics from 1 January 1995, to 12 December 2024. Bibliometric analyses, including publication trends, citation networks, and keyword co-occurrence patterns, were performed using VOSviewer and CiteSpace. Collaborative networks, co-cited references, and keyword burst analyses were mapped to uncover shifts in research focus and global cooperation.ResultsBoth annual publication volume and citation frequency have shown a wave-like increase since 2000. Initially, research activity was limited during the early period (2000-2006), followed by a phase of slow growth between 2007 and 2015. A surge in publications occurred after 2016, peaking in 2022 with 81 articles. Despite the increase in publications, citation frequency declined after 2019, indicating a gap between research output and scholarly impact. The United States, China, and Italy were the top contributing countries, with the U.S. maintaining a leadership role. Keyword analysis revealed key research themes, including biomarkers, uveal melanoma, and immunotherapy, with a shift towards gene expression, tumor metastasis, and liquid biopsy in recent years. Keyword burst analysis identified retinoblastoma protein and gene expression as major research hotspots.ConclusionOcular tumor metabolomics research has made significant strides in recent years. This analysis provides a comprehensive framework for future research, emphasizing the need for interdisciplinary collaborations and the development of non-invasive diagnostic tools to improve the diagnosis, prognosis, and treatment of ocular tumors.